Demographic factors that affect the competence of Cooperative Board Members (CBM) / Adila Hashim, Azianti Ismail, Nur Yazira Hamsan, Siti Nuraini Abu Bakar, Rosmalina Che Yakzam, Norfaezah Mahmood and Nor Irzaq Nor Hamid - Hashim, Adila; Ismail, Azianti; Hamsan, Nur Yazira; Abu Bakar, Siti Nuraini; Che Yakzam, Rosmalina; Mahmood, Norfaezah; Nor Hamid, Nor Irzaq (2024)
Competence is a crucial element in ensuring the success of an organization, especially in the cooperative sector. It is crucial to appoint competent and capable Cooperative Board Members (CBM) to ensure profitability of the entity and efficient management of cooperative activities. This study aims to identify the level of competence of CBM based on demographic factors such as age, education level, and years of experience, across different states in Malaysia. This study employed a quantitative method via a set of survey questionnaire distributed to 420 respondents who are CBM representing diverse demographic backgrounds (different age groups, education level, and years of experience). Simple random sampling was used as the sampling method. The collected data was analysed using Rasch Measurement Model via Winstep 5.2.20. The results of this study indicate that out of the fourteen states in Malaysia, the three states with the highest levels of CBM competence according to logit values are Perak, Sarawak, and Kelantan, while the three states with the lowest levels of CBM competence are Perlis, Pahang, and Kedah. The research findings suggest that factors such as age and education level influence CBM competence level, whereas years of experience does not significantly affect their competence.